Argo float test profile with a HydroFlash O2 optode in the Mediterranean Sea in June 2016 - Tobias Hahn; Henry Bittig (PANGAEA, 2025)
Lab and field experiments were conducted with 13 CONTROS HydroFlash O2 optodes to evaluate the performance of this oxygen sensor. All optodes received pre- and post-deployment calibrations (multi-point and/or two-point), and field data complemented the extensive characterization, facilitating to address information about its salinity and hydrostatic pressure dependence, its stability assessment during storage and deployment, and its time dependence as well as performance on observation platforms.